Theories of change: navigating diverse expert perceptions and preferences for global food system transformation - Loring, Philip A.; Loken, Brent; Bhalla, Iqbal S.; Daniel, Adil; De La Torre, Ana; Friedman, Suzy; Melo-Rijk, Melody; del Rosario, Liezl Stuart; Tardiou, Ariane; van Dooren, Corné; Upadhyay, Gargi (Frontiers in Sustainable Food Systems, 2024)
Introduction Efforts are underway to transform food systems in light of their contributions to global challenges like climate change. However, food systems are highly complex, involve noteworthy place-based challenges, and there is often debate and disagreement among experts over appropriate technologies or interventions to prioritize. Tracking progress, and understanding these differences, is thus a critical need. Methods We surveyed food systems experts in eight countries about their preferences for 20 different food system transformation strategies and their sentiment regarding whether current initiatives are sufficient to meet 2030 goals for climate and biodiversity. Results Expert sentiment is overwhelmingly negative, and experts are concerned about multiple “transformation gaps,” including gaps in ambition, strategy, and implementation. Expert rankings for 20 strategies vary notably among countries and in ways that do not match those same experts’ rankings for the strength of the science behind each lever. Factor analysis reveals four distinct theories of change informing experts’ subjective biases: transformation via technical optimization, via smallholder support, via nature-positive solutions, and via supply chain enabling conditions. Discussion These findings provide insights for navigating the complexities of food system transformation and illustrate the influence on our strategies of preconceptions and biases in how we have come to understand the nature of the challenge.